Could enterprise risk management (ERM) create, protect and enhance shareholders’ wealth among Malaysian listed issuers - Kasim, Mohd Ariff; Mohd Hanafi, Siti Rosmaini (2017)
The primary objective of this study is to explore the extent to which ERM implementation is capable of enhancing shareholders’ wealth. A sample of 283 companies operating in the Main Market of Bursa Malaysia was selected.This study utilized the definition of ERM as the independent variable and shareholders’ wealth as dependent variable.The overall observation revealed that ERM was significant in explaining the variation in shareholders’ wealth.Objective setting, event identification, risk response, control activities, information and communication, and monitoring substantiated the hypothesized relationship. The research framework of this study, which utilized assumptions from stewardship and agency theory, could serve as guidance for future research on organizational control and governance.The study fills the gap in literature which mostly concentrated on the USA and western countries.The CRO and the board should focus more advising functions at the earlier stage of the ERM implementation and monitoring functions once ERM matured.